2021
DOI: 10.3390/ijerph18126318
|View full text |Cite
|
Sign up to set email alerts
|

Media Exposure and Substance Use Increase during COVID-19

Abstract: Background: Lockdown measures because of COVID-19 are likely to result in deteriorating physical and mental health. In this study, our aim was to assess the impact of media exposure on increases in substance use during the COVID-19 pandemic. Methods: A nationally representative online survey of 1264 adults was collected during the pandemic in the United States. Logistic regression was used to explore the association between an increase in substance use since the beginning of the COVID-19 pandemic and exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition, we found that CKD guardians watching the COVID-19-related news for 30–60 min daily were less expected to have depression, compared with the guardians for <10 min. It had been reported that participants with low knowledge of COVID-19 were more likely to experience mental health and more substance use ( 32 ). Besides, increased time spent on social media and consulting more traditional media sources about COVID-19 had been confirmed independently associated with increased mental distress ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that CKD guardians watching the COVID-19-related news for 30–60 min daily were less expected to have depression, compared with the guardians for <10 min. It had been reported that participants with low knowledge of COVID-19 were more likely to experience mental health and more substance use ( 32 ). Besides, increased time spent on social media and consulting more traditional media sources about COVID-19 had been confirmed independently associated with increased mental distress ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sexism is an insidious stressor that can adversely impact health behaviors and outcomes (Homan, 2019; Meyer, 2003), including increased alcohol use (Roberts, 2012; Zucker & Landry, 2007). Similarly, consuming high levels of distressing media can have negative health implications (Alexander et al, 2023; Amram et al, 2021; Ford et al, 2023; Silver et al, 2013). Although it is critical to inform the public of legislative changes, the extensive media coverage of abortion-related issues immediately following the Dobbs ruling may be particularly harmful for women who opposed (vs. supported) the ruling as they may be most distressed by this infringement on reproductive rights.…”
Section: The Present Studymentioning
confidence: 99%
“…The lengthy periods of quarantine and isolation have also been conducive to more substance use ( Masaeli and Farhadi, 2021 , Nagata et al, 2022 ). Although drug use during adolescence is often associated with social situations which to some extent have been curtailed by the COVID-19 pandemic, recent studies have reported significantly increased rates of alcohol, cigarette, and marijuana use among adolescents ( Amram et al, 2021 , Chaffee et al, 2021 , Lundahl and Cannoy, 2021 , Pigeaud et al, 2021 , Villanti et al, 2022 ). A rise in children's and adolescents' technological addictions to the internet, social networks, video games, and mobile phones has also been documented ( Bećirović & Pajević, 2020 ).…”
Section: Introductionmentioning
confidence: 99%